Implementasi Aromaterapi Chamomile Untuk Penurunan Skala Nyeri Pada Pasien Post Sectio Caesarea Dengan Anestesi Spinal di RSUD Dr. Soedirman Kebumen - Ratri, Hong Nuring Madyo; Suryani, Roro Lintang; Yudha, Magenda Bisma (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Background. Sectio caesarea is a surgical process to deliver a fetus through an incision in the abdominal wall and uterine wall. Mechanical incision or treatment that is offered to nociceptor impulses through the process of transduction, transmission, modulation, and perception causes pain in post sectio caesarea patients. One of the non-pharmacological pain treatments is the administration of chamomile aromatherapy. Chamomile can provide anti-inflammatory, antioxidant, and analgesic effects so that it can reduce the pain felt by the mother. Objective. This PkM activity aims to help reduce the pain scale for post sectio caesarea mothers using chamomile aromatherapy. Methods. The method used was patient identification according to PkM characteristics, pre-test to measure the pain scale using a Visual Analog Scale (VAS), and then giving chamomile aromatherapy as much as 2 drops (0.2 ml) on a cotton ball for 15 minutes at a distance of 5 cm, and post-test to measure the pain scale again. Results. The results showed that before the intervention, most of the pain scale experienced moderate pain as many as 23 respondents (76.7%). After the intervention the pain scale decreased to mild pain as many as 20 respondents (66.7%). Conclusion. Chamomile aromatherapy can be applied to reduce the intensity of the pain scale in post sectio caesarea patients. Outputs. The output produced is a pocket book that can be used as a medium for learning nonpharmacological therapy using chamomile aromatherapy as an intervention in reducing pain patients in post sectio caesarea patients. The results of the activity can be published in a Scientific Journal.